2001
DOI: 10.1002/ijc.1538
|View full text |Cite
|
Sign up to set email alerts
|

Primary liver cancer and occupation in men: A case-control study in a high-incidence area in northern Italy

Abstract: The objective of our study was to evaluate the association between occupation and risk of liver cancer. A hospital-based case-control study was carried out during 1997-1999 in the Province of Brescia, a highly industrialized area in Northern Italy with a high incidence of this neoplasm. The cases were 144 male patients with incident liver cancer (96% hepatocellular carcinoma). Controls were 283 male patients, matched to cases on age (؎5 years), period and hospital of admission. Information on lifetime occupati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 29 publications
2
36
0
2
Order By: Relevance
“…There is some evidence that occupational exposure to trichlorethylene (resin solvent), methylene chloride, toluene, and xylene might be associated with an increased risk for liver cancer [Lynge, 1994;Wartenberg et al, 2000;Porru et al, 2001]. A meta-analysis among workers exposed to organic solvents revealed a small risk increase for liver cancer (SMR 144, CI ¼ 118-175) [Chen and Seaton, 1998].…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that occupational exposure to trichlorethylene (resin solvent), methylene chloride, toluene, and xylene might be associated with an increased risk for liver cancer [Lynge, 1994;Wartenberg et al, 2000;Porru et al, 2001]. A meta-analysis among workers exposed to organic solvents revealed a small risk increase for liver cancer (SMR 144, CI ¼ 118-175) [Chen and Seaton, 1998].…”
Section: Discussionmentioning
confidence: 99%
“…If we extend the outcome from HCC to all primary liver cancer, oil refinery workers, plumbers, pipe fitters, cooks, laundry workers, lithographers, and those who work in long-term offset printing or auto repair shops, as well as restaurant and hotel businesses were discovered to be of potential high risk [20,21,50,51]. Workers exposed to solvents, toluene or xylene were also associated with primary liver cancer [19,52]. Recently, a case-control study suggested a mild association between metal machining jobs and HCC among those without viral infection [53].…”
Section: Discussionmentioning
confidence: 99%
“…The results of 1 study suggest an association between longterm exposure to toluene and xylene, 2 of the most common aromatic solvents, and liver cancer. 16 In another study, exposure to thinners, turpentine and white spirit was suggested to be associated with hepatocellular carcinoma. 34 We saw no excess risk of liver cancer among women exposed to aliphatic/alicyclic, aromatic or chlorinated hydrocarbons; thus, confirming the result of a previous Finnish study on gastrointestinal cancers.…”
Section: } } }mentioning
confidence: 97%
“…A more recent Italian study, however, suggested that prolonged exposure to toluene and xylene may represent a risk factor for liver cancer. 16 Benzene has been classified by IARC as carcinogenic, and styrene as possibly carcinogenic to humans, but neither of these aromatic solvents has been associated with liver cancer. 17,18 Some studies on cancer incidence or mortality in occupations, which usually involve exposure to solvents, have shown increased risks of liver cancer.…”
mentioning
confidence: 99%